Gender, social change and spiritual power : charismatic Christianity in Ghana - Soothill, Jane E. (Studies of Religion in Africa, 2007)
Charismatic Christianity is the most recent and fastest growing expression of Pentecostal religion in Sub-Saharan Africa. In Ghana's capital, Accra, the charismatic churches dominate the religious scene. This book focuses on the gender discourses of Ghana's new churches, and considers charismatic perspectives on womanhood, manhood, marriage and family life. Offering a fresh perspective on the organisational structures of the charismatic churches, this study looks at the leadership roles of female pastors and pastors' wives, and draws attention to the links between female leaders and spiritual power. By highlighting the importance of spiritual power in interpreting gendered social change, the book sheds new light on the socio-cultural role of Ghana's new churches.